2016
DOI: 10.5539/gjhs.v9n2p256
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Administration of Pistacia Atlantica Kurdica Gum on the Eradication of Helicobacter Pylori in Patients with Dyspepsia: A Randomized Clinical Trial

Abstract: H. pylori infection is one of the most common infections in the world so that the aim of this study was to evaluate the antimicrobial P. Atlantica Kurdica gum in the eradication of H. pylori. This study is a randomized clinical trial; Patients with positive Urea Breath Test and symptoms of dyspepsia were entered. Patients were randomly divided into four groups. Group A: three drugs including 500 mg of Amoxicillin twice a day (bd), Clarithromycin 500 mg bd and Omeprazole 20 mg (bd) and Group B: Group A drugs pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Roe et al(42) reported that the use of mastic was effective in limiting the concentration of H. pylori, as well as gastritis. The results of Huwez et al(43) and Afrasiabian et al(44) studies showed that Pistacia spp. eradicated H. pylori and improved the symptoms of dyspepsia.…”
mentioning
confidence: 93%
“…Roe et al(42) reported that the use of mastic was effective in limiting the concentration of H. pylori, as well as gastritis. The results of Huwez et al(43) and Afrasiabian et al(44) studies showed that Pistacia spp. eradicated H. pylori and improved the symptoms of dyspepsia.…”
mentioning
confidence: 93%